KONFLIK SOSIAL PADA NOVEL WARISAN KARYA CHAIRUL HARUN - Saputri, Angi; Thahar, Harris Effendi; Hayati, Yenni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This study aimed to describe (1) the form of social conflict in the novel Inheritance works Chairul Aaron, (2) the cause of social conflict in the novel Inheritance works Chairul Aaron, (3) the settlement of social conflict in the novel Inheritance works Chairul Aaron. The research is a qualitative descriptive method. The approach taken in this study is the approach of sociology of literature. Data of this study are the elements of the novel that reveals social conflicts contained in the novel Inheritance work Chairul Harun include: (1) the forms of social conflict in the novel Inheritance works Chairul Aaron, (2) the cause of social conflict in the novel Inheritance works Chairul Aaron , (3) the forms of social conflict resolution in the novel Inheritance works Chairul Aaron. This research data collection techniques are read and understand, identify, inventory, and mengklasisifikasikan data relating to social conflict in the novel Inheritance works Chairu Aaron. Based on the research results, it can be concluded social conflict in the novel Inheritance Chairul Aaron's work as follows. First, the forms of social conflict, namely; personal conflicts as a result of another person; The main figures conflict with the family; The main figures conflict with the community. Second, penyebabtimbulnya social conflict, namely; economic factors; biological factors; psychological factors; cultural factors. Third, the forms of social conflict resolution, namely conciliation / peace; mediation; coercion / force; détente / loosening. This research may be implicated in learning Indonesian curriculum SBC / 2006 class XI 1st half at SK. 7 Finding elements of intrinsic and extrinsic saga, with KD7.2 Analyzing the intrinsic elements novel Indonesia / translation. Kata kunci: konflik sosial, novel, implikasi